1970
DOI: 10.3329/taj.v15i2.3916
|View full text |Cite
|
Sign up to set email alerts
|

Inserted Needle in the Abdominal Wall

Abstract: A 20 year old housewife presented with multiple needles in her abdominal wall as revealed by radiological examination. She had unrelated symptoms but the needles were more or less silent for months except one group caused foreign body granuloma formation. Exploration and removal of four of these needles were done under general anaesthesia. Deliberately inserted needles in the abdominal wall are very unusual, which is not yet reported to our knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…One study included two cases of SEB . Three additional studies were found in reference lists (see Fig. and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…One study included two cases of SEB . Three additional studies were found in reference lists (see Fig. and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…One arises from the distal portion of the sacrococcygeal region, is clinically obvious from birth and nearly always benign. Another type arises proximally in the retrorectal or adjacent retroperitoneum, noticed after birth, usually gonadal origin and malignant from the start [6].…”
Section: Introductionmentioning
confidence: 99%